Building Sustainable Islamic Education: The Power of Innovative Entrepreneurship Education Management - Najihah, Iffatun; Wahidmurni, Wahidmurni; Tharaba, M Fahim (JURNAL AL-TANZIM, 2025)
This study examines innovative management in entrepreneurship education that integrates Islamic values with environmental sustainability in Islamic schools. The primary focus of this research is active collaboration between Islamic schools and external partners as a strategy to build a sustainable entrepreneurial ecosystem. Using a qualitative approach with a case study, data collection techniques included interviews, observation, and documentation. Data analysis was conducted using a thematic analysis approach to identify patterns within the data. The results indicate that through instilling the values of khalifah fil ardh (vicegerent) and hifdzul bi'ah (leadership), utilizing local waste as production materials, integrating the curriculum, extracurricular activities, and external collaboration, the Islamic school successfully created a holistic entrepreneurial ecosystem. This innovation significantly increased students' independence, skills, and systematic thinking, while strengthening the role of teachers as facilitators and mentors. The implications of this research demonstrate the importance of integrating Islamic values and environmental sustainability in entrepreneurship education in Islamic schools. This holistic approach can serve as a model for other Islamic schools in building independent entrepreneurial ecosystems while strengthening the role of teachers as facilitators in creating an innovative and responsible generation.